Allopurinol treatment and its effect on renal function in gout: a controlled study. Issue 1 (February 1982) - Gibson, T; Rodgers, V; Potter, C; Simmonds, H A
Abstract : Fifty-nine patients with primary gout were treated with either a combination of colchicine and allopurinol or colchicine alone. Assessments of renal function over 2 years revealed a statistically significant fall of glomerular filtration rate an urine concentrating ability in those receiving only colchicine. The renal function of patients given allopurinol did not change. Treatment with allopurinol resulted ina significant reduction of ammonium excretion, a phenomenon which could not be readily explained. Urate clearance also declined during allopurinol treatment, and the impaired urate clearance associated with gout became more evident. The most important observation was that allopurinol retarded an apparent decline of renal function. Presumably this was achieved through its hypouricaemic effect and implies that the hyperuricaemia of gouty patients is deleterious to the kidneys.